Immune-mediated adverse events post-COVID vaccination and types of vaccines: a systematic review and meta-analysis - Hind A. ElSawi; Ahmed Elborollosy (SpringerOpen, 2022)
Abstract Background In late 2019, Coronavirus disease 2019 has been declared as a global emergency by World Health Organization. Hopefully, recent reports of effective and safe vaccines were welcomed, and approved on emergency base. Millions of recipients had received one of the approved COVID 19 vaccines, with lots of adverse events recorded global wide. Objective To assess post-COVID vaccination immune-mediated adverse events and evaluate its association to specific type of vaccine global wide. Methods Systematic literature review and meta-analysis of published reports (since December 2020 till December 2021) on immune-mediated adverse events post-COVID vaccination. Results We evaluated 34 published studies; 460 cases with various adverse events post-COVID vaccination. Studies in current literature are primarily retrospective case series, isolated case reports or narrative studies. Different COVID vaccines were involved. Results' data was subcategorized according to associated vaccine. Adverse effects of COVID-19 vaccinations included thrombotic, neurological, myocarditis, ocular, dermatological, renal, hematological events timely linked to inoculation. Each vaccine type was linked to adverse profile that differ from others. Conclusion High suspicion of post-vaccination adverse events is mandatory to provoke earlier detection, better understanding, optimum prevention, and management. Specific vaccine/patient risk profile is needed to selectively categorize target population to reduce morbidity and mortality post-vaccination.